EFFICACY OF DICLOFENAC COMPARED TO PLACEBO IN PAIN RELIEF DURING REMOVAL OF URETHRAL CATHETER - Maulana, Akhada; Danarto, H R (Indonesian Urological Association, 2010)
Objective: To investigate efficacy of diclofenac compared to placebo in relieving pain on removal of indwelling urethral catheters. Materials and methods: This study was a randomized controlled trial, double blind, comparing diclofenac with placebo in relieving pain on removal of indwelling urethral catheters. Adult male patients with indwelling catheters admitted in surgical ward of RSUP Dr. Sardjito Yogyakarta who met the inclusion criteria were recruited. The independent variables were diclofenac or placebo treatment, while the dependent variables were visual analogue scale (VAS) score, and the external variables were age, education level, and duration of indwelling urethral catheter. We gave patients diclofenac or placebo in capsules 2 hours before urethral catheter removal. Immediately after removal by assistant, the patient filled VAS form. We used Chi-square test, independent T-test, and bivariate analysis with SPSS program version 11.5, with p<0,05 was set as statistically significant level. Results: Thirty patients met inclusion criteria. Mean VAS score of both groups was 33,467 + 20,4577, diclofenac group was 31,567 + 20,0934, and placebo group was 35,367 + 21,3412. There was no statistically significant difference of VAS score between both groups (p=0,844). Conclusion: Efficacy of diclofenac and placebo in relieving pain when performing urethral catheter removal is not significantly different.